2(x+4)=x+6

Simple and best practice solution for 2(x+4)=x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+4)=x+6 equation:


Simplifying
2(x + 4) = x + 6

Reorder the terms:
2(4 + x) = x + 6
(4 * 2 + x * 2) = x + 6
(8 + 2x) = x + 6

Reorder the terms:
8 + 2x = 6 + x

Solving
8 + 2x = 6 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
8 + 2x + -1x = 6 + x + -1x

Combine like terms: 2x + -1x = 1x
8 + 1x = 6 + x + -1x

Combine like terms: x + -1x = 0
8 + 1x = 6 + 0
8 + 1x = 6

Add '-8' to each side of the equation.
8 + -8 + 1x = 6 + -8

Combine like terms: 8 + -8 = 0
0 + 1x = 6 + -8
1x = 6 + -8

Combine like terms: 6 + -8 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| 6u=5u-8 | | 6+3x=1x | | 5=4x+6x+5 | | 10=-6k+k | | -6=-2n | | 5(3-2x)-3(4-2x)=19 | | 7x+4+2x=-1 | | -8.1=y+7.8 | | 5x+9y=96 | | 5(x+2)-4(x-1)=6 | | 4(7y+2)=3(9y-2) | | 3x+4=10x-3 | | 4(x+3)-2x=7 | | 1+m+3m=-19 | | x^2-3x-12=20 | | 4(x-3)-2(x-1)=-6 | | -8x+3x+7=47 | | 2(x+2)=2(3x-2) | | 3-2x=-15 | | 9x+3y=-8 | | 32=-4m+8 | | 40X^2+131X+105=0 | | 15x-6=8x+4 | | 3y-6=-18 | | 3+4X=4-5 | | -15x-10=-10x | | 7-2x=-14 | | y+34=5 | | 3x^2=x+24 | | 7y-5=y-1 | | y+30=5 | | y+3-2=5 |

Equations solver categories